Development of an IoT-Based Soil Sensor Practical Tool Integrated with Performance Assessment to Improve Critical Thinking in Grade X High School Students - Rista, Gelar; Diawati, Chansyanah; Rosidin, Undang; Fadiawati, Noor; Herlina, Kartini (Postgraduate, University of Mataram, 2026)
The world of education requires practical tools that are not just demonstrations, but also provide relevant active learning experiences that trigger curiosity and fulfill 21st-century skills, namely critical thinking. This study aims to evaluate the effectiveness of an IoT-based soil sensor practical tool integrated with performance assessment in improving students' critical thinking skills. This study used an embedded mixed-methods experimental design, with a purposive sampling technique to select two classes with similar levels of critical thinking at the beginning of the study. The study involved pre-tests and post-tests in the experimental and control classes. The results showed that the experimental class experienced a significant increase in critical thinking skills, with a post-test score increasing sharply from 48.54 to 90.42, while the control class only increased from 56.60 to 72.99. A significant difference between the two classes was revealed through the ANCOVA test (p = 0.000), which showed that the use of IoT-based tools had a significant impact on students' critical thinking skills, with a Partial Eta Squared of 0.550. Thus, the IoT-based soil sensor practical tool integrated with performance assessment has proven effective in encouraging the improvement of students' critical thinking skills, making it an innovative solution in more interactive and applicable science learning.